(3caGjI GdeJMaX hfgGjI GdeJdaXs - (3CHh ESMGb Hf EHQGgje Hf ESeGYjd Hf CMeO, GdCLOGHj GdWQGHdSj s ((3MdH s)
(3ChdgG (B:s
(3bGd GdTjN GdCLOGHi GdWQGHdSi GdMeO ddg QH GdYGdejf gPG cJGH eNJUQ ai GddZI heG jMJGL Edjg ef ZQjH GdcdGe GdLhGO GdQLd GdSNi s
(3BNQgG (B:s
(3hGdhWjS TF jTHg GdJfhQhjNJHQ ajg hGdfHQGS GdeUHGM hGdPHGdI GdaJjdI hLeYgG PHGd hgj GdTYjdI CjVkG hLeYgG TYGFd hGddgg CYde fLRJ caGjI GdeJMaX s
(3HgG fXGe GdJYbjHIs
(3YdjgG bQGAI hebGHdI ai SfI (B614(3g`s
(3fSNI KGdKIs
(3jhLO GjVG JMJ Qbe (B2885 s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GddZIs